Moral compass - Steel, Danielle (New York : Random House Large Print Publishing, 2020)
"One day after the school$1 (Bs annual Halloween event, a student lies in the hospital, her system poisoned by dangerous levels of alcohol. Everyone in this sheltered community$1 (Bparents, teachers, students, police, and the media$1 (Bare left trying to figure out what actually happened. Only the handful of students who were there when she was attacked truly know the answers and they have vowed to keep one another$1 (Bs secrets. As details from the evening emerge, powerful families are forced to hire attorneys and less powerful families watch helplessly. Parents$1 (Bmarriages are jeopardized, and students$1 (Bfutures are impacted. No one at Saint Ambrose can escape the fallout of a life-altering event."--s
Keywords: Students -- Fiction; Private schools -- Fiction; Large type books